High-Throughput Metabolomics for Identification of Metabolic Pathways and Deciphering the Effect Mechanism of Dioscin on Rectal Cancer From Cell Metabolic Profiles Coupled With Chemometrics Analysis - Wang, Xin-Xin; Yu, Peng-cheng; Li, Jun (Frontiers in Pharmacology, 2020)
High-throughput liquid chromatography–mass spectrometry (LC-MS)-based metabolomics can provide the holistic identification and quantification measurement of all small endogenous metabolites in cells, reflect the changes of cellular regulation and signaling pathways in physiopathologic states. The present study aimed to reveal the potential pharmacological activity of Dioscin on SW480 rectal cancer cells using non-targeted metabolomics method to probe into small molecular metabolites and pathway changes. LC-MS-based non-targeted metabolomics was employed to profile the metabolic profiles of human SW480 rectal cancer cells treated with Dioscin. After chemometrics analysis, 22 metabolites were selected as potential predictive biomarkers of pharmacodynamic response of Dioscin to rectal cancer, and eight highly correlated pathways including D-glutamine and D-glutamate metabolism, pyruvate metabolism, arachidonic acid metabolism, phenylalanine metabolism, tryptophan metabolism, glycolysis or gluconeogenesis, citrate cycle (TCA cycle) and butanoate metabolism were identified. Dioscin reduces the capacity of cell proliferation, migration and invasion, and promote the capacity of cell apoptosis. Cell metabolomics focuses on the in-depth research of all small molecular metabolites from cell biological systems, which is a promising tool for new drug discovery from natural products.